Estimating the Effectiveness of Pfizer and Sinopharm Vaccines and their Relationship to Occupation, Residence, Smoking, and Body Mass Index During Pregnancy Smoking - Shahad Th. Jameel; Asmaa Haseeb Hwaid; Abdulrazak SH. Hasan (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a rapid global demand for the development of several vaccines by the scientific community. Vaccination contributes to preventing infection associated with symptoms and reduces the risk of infection by stimulating the immune system to produce antibodies. This study aimed to determine the effectiveness of Pfizer and Sinopharm vaccines and their relationship to occupation, residence, pregnancy, mass index, and smoking. This study was conducted in Diyala Province, Iraq, for the period from April 2022 to May 2023. A total of 266 blood samples were collected. Written consent was obtained by the Research Ethics Committee in the Diyala Health Department(DHD/No-39072/Date-31/8/2022).The researchers collected the data using a specific questionnaire they created after conducting a brief interview with the participants. The ELISA technique was used to detect IgG titers. The rate of positivity for IgG antibodies among study participants vaccinated in Diyala province was 53.8%, and the Mean±SD for those vaccinated with the Pfizer vaccine was higher compared to the Mean±SD for those vaccinated with the Sinopharm vaccine, and the statistical difference was significant. Despite the higher antibody titer among participants residing in Khanaqin compared to those from other locations, the current results indicate no significant differences in antibody titer based on the participants' place of residence (P = 0.474). The study revealed no statistically significant influence of mass weight, blood groups, and rhesus factor on antibody titres. As for smoking, the study participants who smoked had a lower titer compared with non-smokers, with a statistically significant difference (P = 0025). The study concluded that the overall protective rate of SARS-CoV-2 vaccines among participants in Diyala Governorate after twelve to seventeen months of vaccination was good, and that the Pfizer mRNA vaccine had a better outcome compared to the inactivated Sinopharm vaccine.